2013
DOI: 10.1055/s-0032-1328266
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Malignant Cervical, Corpus Uteri and Ovarian Tumours - Current Data and Epidemiological Trends

Abstract: Introduction !In addition to breast cancer, gynaecological malignancies also include cervical, endometrial and ovarian cancers. Cancer of the corpus uteri is the most common malignancy of the female genital tract, followed by ovarian and cervical cancer.In Germany, these malignancies account respectively for 5.1 % (fourth most common malignancy in women), 3.5 % (sixth most common) and 2.2 % (twelfth most common) of all newly diagnosed cancers in women. As most cervical and endometrial cancers, particularly oes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 13 publications
0
31
0
1
Order By: Relevance
“…Similar results were found by Waldmann et al, who reported a decrease in incidence and mortality of OC among a German population during the last two decades. 34 Another study reported stable OC incidence and mortality rates in Nordic countries for 1964–2003. 35 Interestingly, despite the decreasing fertility rate and parity, we observed a decrease in the OC incidence in the analyzed population.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found by Waldmann et al, who reported a decrease in incidence and mortality of OC among a German population during the last two decades. 34 Another study reported stable OC incidence and mortality rates in Nordic countries for 1964–2003. 35 Interestingly, despite the decreasing fertility rate and parity, we observed a decrease in the OC incidence in the analyzed population.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial ovarian carcinoma (EOC) is the most lethal gynecological malignancy (Siegel et al, 2012). Most patients with EOC are diagnosed at an advanced stage and although most initially respond to cytoreductive surgery and platinum-based chemotherapies, many EOC patients eventually relapse, develop chemoresistant tumors, and die because of the disease (Ozols, 2006;Waldmann et al, 2013). As the empirical incorporation of additional cytotoxic agents against ovarian cancer does not improve prognosis (Bookman et al, 2009), understanding the key signaling pathway responsible for chemoresistance and disease progression is required to develop new treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…About 14,000 of these women are expected to die of the disease [ 1 ]. In Germany the corresponding figures are 7400 and 5500 [ 2 ]. This high mortality rate is mainly the consequence of ineffective early detection or screening programs.…”
Section: Introductionmentioning
confidence: 99%